Cloud based mobile inventory application / Muhammad Nazerul Saifulazhar - Saifulazhar, Muhammad Nazerul (2015)
Mobile Computing is a technology that lets transmission of data, via a computer, deprived of having to be connected to a fixed physical link (Vasilis Koudounas, 2009). Mobile computing lets people to contact network services anyplace, anytime and anywhere. Cloud computing for mobile devices is a very interesting and potentially profitable trend (Shanklin, 2010). Applications in mobile computing support how mobile software service can use in order to simplify the mobile user’s life. Applications of mobile computing include bank transaction, retail purchases and inventory managing system for small medium and enterprises (jlivi, 2013).